A New Perspective on Key Expansion for QKD BB84: The RanA Model - Mello, Thiago Luigi; Sant’Anna, Isys; Freire, Marcus; Maia, Adriano; Moreira, Rodrigo; Rivelino, Roberto; Peixoto, Maycon (Anais do Workshop de Redes Quânticas (WQuNets), 2025)
Quantum cryptography, exemplified by the BB84 protocol, ensures secure key distribution through quantum mechanical principles such as superposition and the no-cloning theorem. However, limitations in key generation rates and scalability, along with attenuation and noise in quantum channels, hinder its practical deployment in high-demand scenarios. This study proposes a hybrid approach that combines BB84 with classical key expansion, reducing dependence on quantum channels while maintaining efficiency and robustness against quantum attacks. The experimental results validate the scalability and security of the protocol.